2016
DOI: 10.1128/jvi.02995-15
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of the Chronic Hepatitis C Virome Defines Hypervariable Region 1 Evolutionary Phenotypes in the Context of Humoral Immune Responses

Abstract: Hypervariable region 1 (HVR1) of hepatitis C virus (HCV) comprises the first 27 N-terminal amino acid residues of E2. It is classically seen as the most heterogeneous region of the HCV genome. In this study, we assessed HVR1 evolution by using ultradeep pyrosequencing for a cohort of treatment-naive, chronically infected patients over a short, 16-week period. Organization of the sequence set into connected components that represented single nucleotide substitution events revealed a network dominated by highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…This is supported by the correlation between persistence and higher non-synonymous to synonymous substitution rates in HVR1 ( 142 ), thus indicating that HVR1-directed immune responses can help the virus persist. The observed positive selection of HVR1 ( 101 103 ), combined with studies of HVR1 variants in immune-complexed HCV further supports this hypothesis ( 143 , 144 ). In addition, the appearance of HVR1-specific antibodies in patient sera was associated with emergence of immune-complexes of particles carrying that specific HVR1 sequence, leading to a large reduction of that viral population within the patient ( 144 ).…”
Section: Hvr1 Protects Hcv From Neutralizing Antibodiesmentioning
confidence: 52%
See 1 more Smart Citation
“…This is supported by the correlation between persistence and higher non-synonymous to synonymous substitution rates in HVR1 ( 142 ), thus indicating that HVR1-directed immune responses can help the virus persist. The observed positive selection of HVR1 ( 101 103 ), combined with studies of HVR1 variants in immune-complexed HCV further supports this hypothesis ( 143 , 144 ). In addition, the appearance of HVR1-specific antibodies in patient sera was associated with emergence of immune-complexes of particles carrying that specific HVR1 sequence, leading to a large reduction of that viral population within the patient ( 144 ).…”
Section: Hvr1 Protects Hcv From Neutralizing Antibodiesmentioning
confidence: 52%
“…One study, finding no evidence of positive selection and no correlation between evolutionary rate and HVR1-specific antibody responses in patients, suggested that random drift might be the cause for HVR1 variation ( 100 ). However, many studies did observe strong positive selection of HCV, particularly in HVR1 ( 101 103 ) and a large body of data now supports that HVR1 variation is due to antibody-driven immune selection. Firstly, antibodies against HVR1 are commonly detectable in chronically infected patients ( 37 , 104 110 ) and the early induction of such antibodies is associated with acute self-limited infection ( 111 ).…”
Section: Characterization Of Hvr1 In Patient Studiesmentioning
confidence: 99%
“…The distribution of mutations along the HCV genome differed from the distribution observed when comparing clinical isolates (69)(70)(71)(72). In particular, it is noteworthy that hypervariable regions 1 and 2 (HVR1 and HVR2) in HCV p200 include only 1 amino acid replacement relative to HCV p0 (1.78% of the total versus 66% of the total within NS5A turbed environment constitutes an ideal scenario to test the molecular-clock hypothesis with an RNA virus.…”
Section: Discussionmentioning
confidence: 88%
“…We have observed that the host humoral immune system targets viral variants which are often clonotypic in nature [2123]. Data from previous research has shown that total IgGs obtained from sera lacking detectable AAV were unable to target viral variants from the pool of quasispecies.…”
Section: Introductionmentioning
confidence: 99%